2023
DOI: 10.1039/d2ta07293a
|View full text |Cite
|
Sign up to set email alerts
|

Method to determine the oxygen reduction reaction kinetics via porous dual-phase composites based on electrical conductivity relaxation

Abstract: The kinetics for the oxygen reduction reaction (ORR) via porous dual-phase composites are critical for high-temperature electrochemical devices such as solid oxide fuel cells. Herein, a method is proposed to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…The interaction of LSM with Zr-containing electrolytes, as it was mentioned above, results in the formation of low conducting LZO and, at high strontium content, SZO phases at the electrode sintering stage at temperatures above 1000-1200 °C, depending on the material dispersity [85]. It has also been found that Mn readily dissolves in YSZ, leaving chemically active La2O3 at the LSM/YSZ interface, which reacts with ZrO2 to form LZO [114]. To reduce the interaction of LSM with Zr-containing electrolytes, the use of (LS)xM, a cation deficient in the A position, has been proposed [129].…”
Section: Optimization Of the Oxide Compositionmentioning
confidence: 89%
See 3 more Smart Citations
“…The interaction of LSM with Zr-containing electrolytes, as it was mentioned above, results in the formation of low conducting LZO and, at high strontium content, SZO phases at the electrode sintering stage at temperatures above 1000-1200 °C, depending on the material dispersity [85]. It has also been found that Mn readily dissolves in YSZ, leaving chemically active La2O3 at the LSM/YSZ interface, which reacts with ZrO2 to form LZO [114]. To reduce the interaction of LSM with Zr-containing electrolytes, the use of (LS)xM, a cation deficient in the A position, has been proposed [129].…”
Section: Optimization Of the Oxide Compositionmentioning
confidence: 89%
“…Automated methods developed for the detection of Sr nucleation seeds on the electrode surface [109,110], for the identification of the interlayer width between the perovskite and YSZ layers [111,112], and for the computational design and numerical simulation of the perovskite-based composite electrodes [113][114][115][116] allowed for the suggestion of possible degradation mechanisms and an understanding of the electrode behavior at both the atomic and macroscopic scales. The deposition of protective and noncatalytic layers on the electrode surface has been proposed as a solution to the problems of segregation [117][118][119], contaminant poisoning [120][121][122][123], and sluggish oxygen kinetics [124][125][126][127][128].…”
Section: Key Functional Properties Of Lsm and Lscf Electrode Material...mentioning
confidence: 99%
See 2 more Smart Citations
“…Decreased Δ p must result in a reduced ORR rate and consequently prolonged t e . 69 It takes much longer for the porous material than the dense material to obtain an evenly distributed oxygen partial pressure while reaching the highest Δ p everywhere. The simulation assumption indicates that uniform oxygen partial pressure cannot be achieved in porous material as quickly as in dense material.…”
Section: Discussionmentioning
confidence: 99%